Natural products: promising therapeutics for targeting regulatory immune cells in the tumor microenvironment - Song, Peng; Song, Fei; Shao, Tingting; Wang, Pengjuan; Li, Rongkun; Chen, Zhe-Sheng; Zhang, Zhaofang; Xue, Guozhong (Frontiers in Pharmacology, 2024)
Regulatory immune cells regulate immune responses through various mechanisms, affecting the occurrence, development, and therapeutic effects of tumors. In this article, we reviewed the important roles of regulatory immune cells, such as Tregs, Bregs, MDSCs, DCregs, and TAMs, in the tumor microenvironment. The immunomodulatory effects of natural products, such as polysaccharides, polyphenols, glycosides, alkaloids, terpenoids, quinones, and other compounds, which affect the functions of regulatory immune cells through molecular signaling pathways, thereby enhancing the potential of the antitumor immune response, are discussed. These findings provide new ideas and possibilities for the application of natural products in tumor treatment, which can help enhance the effectiveness of tumor treatment and improve patient prognosis.